MOG-IgG in NMO and related disorders: a multicenter study of 50 patients. Part 2: Epidemiology, clinical presentation, radiological and laboratory features, treatment responses, and long-term outcome. Issue 1 (December 2016) - Jarius, Sven; Ruprecht, Klemens; Kleiter, Ingo; Borisow, Nadja; Asgari, Nasrin; Pitarokoili, Kalliopi; Pache, Florence; Stich, Oliver; Beume, Lena-Alexandra; Hümmert, Martin; Ringelstein, Marius; Trebst, Corinna; et al.
Abstract Background A subset of patients with neuromyelitis optica spectrum disorders (NMOSD) has been shown to be seropositive for myelin oligodendrocyte glycoprotein antibodies (MOG-IgG). Objective To describe the epidemiological, clinical, radiological, cerebrospinal fluid (CSF), and electrophysiological features of a large cohort of MOG-IgG-positive patients with optic neuritis (ON) and/or myelitis (n = 50) as well as attack and long-term treatment outcomes. Methods Retrospective multicenter study. Results The sex ratio was 1:2.8 (m:f). Median age at onset was 31 years (range 6-70). The disease followed a multiphasic course in 80% (median time-to-first-relapse 5 months; annualized relapse rate 0.92) and resulted in significant disability in 40% (mean follow-up 75 ± 46.5 months), with severe visual impairment or functional blindness (36%) and markedly impaired ambulation due to paresis or ataxia (25%) as the most common long-term sequelae. Functional blindness in one or both eyes was noted during at least one ON attack in around 70%. Perioptic enhancement was present in several patients. Besides acute tetra-/paraparesis, dysesthesia and pain were common in acute myelitis (70%). Longitudinally extensive spinal cord lesions were frequent, but short lesions occurred at least once in 44%. Fourty-one percent had a history of simultaneous ON and myelitis. Clinical or radiological involvement of the brain, brainstem, or cerebellum was present in 50%; extra-opticospinal symptoms included intractable nausea and vomiting and respiratory insufficiency (fatal in one). CSF pleocytosis (partly neutrophilic) was present in 70%, oligoclonal bands in only 13%, and blood-CSF-barrier dysfunction in 32%. Intravenous methylprednisolone (IVMP) and long-term immunosuppression were often effective; however, treatment failure leading to rapid accumulation of disability was noted in many patients as well as flare-ups after steroid withdrawal. Full recovery was achieved by plasma exchange in some cases, including after IVMP failure. Breakthrough attacks under azathioprine were linked to the drug-specific latency period and a lack of cotreatment with oral steroids. Methotrexate was effective in 5/6 patients. Interferon-beta was associated with ongoing or increasing disease activity. Rituximab and ofatumumab were effective in some patients. However, treatment with rituximab was followed by early relapses in several cases; end-of-dose relapses occurred 9-12 months after the first infusion. Coexisting autoimmunity was rare (9%). Wingerchuk's 2006 and 2015 criteria for NMO(SD) and Barkhof and McDonald criteria for multiple sclerosis (MS) were met by 28%, 32%, 15%, 33%, respectively; MS had been suspected in 36%. Disease onset or relapses were preceded by infection, vaccination, or pregnancy/delivery in several cases. Conclusion Our findings from a predominantly Caucasian cohort strongly argue against the concept of MOG-IgG denoting a mild and usually monophasic variant of NMOSD. The predominantly relapsing and often severe disease course and the short median time to second attack support the use of prophylactic long-term treatments in patients with MOG-IgG-positive ON and/or myelitis.